Heritage language identity matters: Tracing the trajectory of a Chinese heritage mother and contested Chinese dual language bilingual education - Lee, Vashti Wai Yu; Her, Lee; De Costa, Peter I. (Studies in Second Language Learning and Teaching, 2024)
This article presents a narrative inquiry of a Chinese heritage mother to theorize and explicate how historical, relational, and spatial processes impacted her negotiation with power and agency in relation to her own heritage language (HL) identity development. A narrative approach enables us to draw on participant counter-stories against master narratives that erase experiences of marginalization of Asians in Asian language education in the United States. We do this through a model of HL identity development (Zhou & Liu, 2022) supplemented by an AsianCrit lens (Iftikar & Museus, 2018). We show the importance of normalizing Chinese as a HL outside of the home in terms of language maintenance as well as the impact such normalization has on the development of an affirmative Chinese HL identity. We add that spaces for such identity development are deeply associated with language programs like dual language bilingual education (DLBE), especially as the number of DLBE opportunities grow in number and in popularity. Thus, language programs, including DLBE, have a responsibility to ensure that the language education they provide address the interests and investments of families with respect to their HL in order to decenter a primary focus on the interests of ethnolinguistic majoritized families.